Decreased anterograde transport coupled with sustained retrograde transport contributes to reduced axonal mitochondrial density in tauopathy neurons - Sabui, Anusruti; Biswas, Mitali; Somvanshi, Pramod Rajaram; Kandagiri, Preethi; Gorla, Madhavi; Mohammed, Fareed; Tammineni, Prasad (Frontiers in Molecular Neuroscience, 2022)
Mitochondria are essential organelle required for neuronal homeostasis. Mitochondria supply ATP and buffer calcium at synaptic terminals. However, the complex structural geometry of neurons poses a unique challenge in transporting mitochondria to synaptic terminals. Kinesin motors supply mitochondria to the axonal compartments, while cytoplasmic dynein is required for retrograde transport. Despite the importance of presynaptic mitochondria, how and whether axonal mitochondrial transport and distribution are altered in tauopathy neurons remain poorly studied. In the current study, we have shown that anterograde transport of mitochondria is reduced in P301L neurons, while there is no change in the retrograde transport. Consistently, axonal mitochondrial abundance is reduced in P301L neurons. We further studied the possible role of two opposing motor proteins on mitochondrial transport and found that mitochondrial association of kinesin is decreased significantly in P301L cells. Interestingly, fitting our experimental data into mathematical equations suggested a possible rise in dynein activity to maintain retrograde flux in P301L cells. Our data indicate that decreased kinesin-mediated transport coupled with sustained retrograde transport might reduce axonal mitochondria in tauopathy neurons, thus contributing to the synaptic deficits in Alzheimer’s disease (AD) and other tauopathies.